Effective adsorption of phenolic pollutants from water using β-cyclodextrin polymer functionalized Fe3O4 magnetic nanoparticles. Issue 84 (26th August 2016) - Gong, Tao; Zhou, Yehong; Sun, Linlin; Liang, Wenting; Yang, Jun; Shuang, Shaomin; Dong, Chuan
Abstract : β-Cyclodextrin polymer functionalized magnetic nanoparticles possess adsorption properties favorable for the purpose of removing phenolic pollutants. Abstract : β-Cyclodextrin polymer functionalized magnetic nanoparticles (CDP-MNPs) were prepared with a one-step co-precipitation method by anchoring a carboxymethyl-β-cyclodextrin polymer (CDP) onto the surface of Fe3 O4 magnetic nanoparticles (MNPs). The CDP-MNPs possess the fascinating features of superparamagnetism and adsorption properties, which are favorable for the purpose of removing bisphenol A and resorcin. The maximum adsorption capacity for bisphenol A could reach values up to 74.63 mg g −1 at 25 °C, which is higher than those of previously reported magnetic adsorbents. Moreover, for the removal of resorcin by CDP-MNPs, the maximum uptake amounted to 114.91 mg g −1 under the same conditions. The adsorption kinetics and isotherm data fitted well with a pseudo-second-order kinetic model and the Langmuir isotherm, respectively. The CD polymer grafted onto the MNPs enhanced the adsorption capacity because of the host–guest interaction of cyclodextrin and the hydrogen bonding of the polymer network with the phenolic compounds. Additionally, a good recyclability of the CDP-MNPs was observed over three usage cycles, with only a slight decline in adsorption capability.